Persönlichkeit der Fussballer AMP Futbol = Personality footballers AMP Futbol - Paweł Kalinowski; Marta Lischka Ołpińska (Journal of Education, Health and Sport, 2016)
Kalinowski, Paweł, Lischka Ołpińska, Marta . Persönlichkeit der Fussballer AMP Futbol = Personality footballers AMP Futbol. Journal of Education, Health and Sport. 2016;6(8):227-235. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60260